Vulvovaginitis and their correction in patients with cervical HPV-associated diseases in the light of the doctrine of pathomorphosis - Irina N. Kononova; Yuliya E. Dobrokhotova; Elena N. Kareva; Olga E. Semioshina; Nadezhda A. Shmakova (IP Berlin A.V., 2021)
Background. Biological pathomorphosis of the leading pathogens of the vaginal microecological system with the occurrence of vulvovaginitis in human papillomavirus (HPV)-associated cervical intraepithelial neoplasia (CIN) is a fundamental prerequisite for optimizing the complex treatment of this disease. Aim. Optimization of treatment of vulvovaginitis based on the study of the pathomorphism of their pathogens in patients with HPV-associated CIN. Materials and methods. A two-stage examination of 211 patients with HPV-associated CIN I was carried out from 2013 to 2020. To study the pathomorphosis of the disease, the patients were divided into 2 groups, the 1st group was examined in 20132016, the 2nd in 20172020. The study of microbiocenosis was carried out by RT-PCR using Femoflor-16 reagents. At the second stage, a study of the clinical efficacy of treatment of vulvovaginitis with the complex drug nifuratel 500 mg + nystatin 200 thousand IU (Macmiror Complex) in comparison with metronidazole 500 mg. Results and discussion. It was revealed that patients with HPV-associated CIN I over the last 8 years have a pathomorphosis of pathogens. In particular, the change in the dominance of anaerobic dysbiosis with the highest bacterial replication of Gardnerella vaginalis in association with Clostridium, Megasphaera spp. and Fusobacterium on the mixed nature of microflora, manifested in the form of vulvaginitis with the dominance of Atopobium vaginae in association with G. vaginalis, Ureaplasma (urealyticum + parvum) and the addition of the intestinal group Enterobacteriaceae spp. and Escherichia coli. The use of the complex drug nifuratel 500 mg + nystatin 200 thousand IU (Macmiror Complex) demonstrated a higher (4 times) clinical efficacy, a 12-fold decrease in the recurrence of the inflammatory process compared with metronidazole in the treatment of vulvovaginitis in patients with CIN I. Conclusions. 1. The structure of the cervico-vaginal microbiota in HPV-associated CIN I degree is characterized by dysbiotic disorders in 68.3% of cases. During the last 8 years, there was a pathomorphosis of the microecological status from the dominant anaerobic (in 74.2% of cases, =9.39 at p=0.001) to the dominant mixed (in 60.8% of cases, =8.54 at p=0.001 ) with the addition of the intestinal group Enterobacteriaceae spp. and E. coli in 60.8% of patients (=9.59 at p=0.001), which indicated a change in the dominant causative agents of vulvovaginitis in CIN I. 2. Comparative analysis of the clinical efficacy of complex drugs has demonstrated an increase in clinical efficacy when using the drug nifuratel 500 mg + nystatin 200 thousand IU by 4 times, a decrease in the recurrence of the inflammatory process by 12 times, compared with standard therapy with metronidazole, which allows us to recommend inclusion of the drug nifuratel 500 mg + nystatin 200 thousand IU in the therapy of vulvovaginitis in patients with CIN I.